2020
DOI: 10.13106/jafeb.2020.vol7.no6.525
|View full text |Cite
|
Sign up to set email alerts
|

Prudent Financial Management Practices among Malaysian Youth: The Moderating Roles of Financial Education

Abstract: The study aims to investigate the roles of financial education (FE) as a moderator to financial attitude (FA), parental financial socialisation (PFS), and financial literacy (FL) to ensure the success of prudent financial management practices (PFMP) among Malaysian youth. The study was designed quantitatively and employed self-administered questionnaires, which were adopted from previous studies and distributed to 480 youths in Malaysia. The data were analyzed using Partial Least Squares Structural Equation Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
6
11
0
Order By: Relevance
“…The results showed that financial literacy was statistically related to collaborative skills, accountability, problem-solving, and decision-making. The results are consistent with the literature review of Bakar and Bakar (2020) and Compen et al (2020). It was discovered that financial literacy might well be improved through MOOCs and digital learning.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that financial literacy was statistically related to collaborative skills, accountability, problem-solving, and decision-making. The results are consistent with the literature review of Bakar and Bakar (2020) and Compen et al (2020). It was discovered that financial literacy might well be improved through MOOCs and digital learning.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, an autonomous person should also be able to analyze social issues related to his expertise. Accounting graduates are required to have knowledge such as financial statement analysis, financial accounting, financial reporting standards, including the basic principles and concepts of accounting (Bakar & Bakar, 2020) to increase competencies prior to the uptake in the job market (Tresnaningsih et al, 2020). Therefore, before applying for a job, accounting graduates should prepare themselves by developing and deepening accounting knowledge while studying in college.…”
Section: Skillsmentioning
confidence: 99%
“…(BPS Indonesia, 2021). [1] Provinces with the most significant percentage of poor people are in Papua, West Papua, East Nusa Tenggara (NTT), and Maluku. The rate of poor people in Papua was 26…”
Section: Diagram 1: Number and Percentage Of Poor Population 1970 -20...mentioning
confidence: 99%